Modelamiento mediante ecuaciones estructurales (PLS-SEM) de factores clave de la transformación digital - Meza Bernaola, Edwin Claudio (2023)
The purpose of the study was to analyze the relevant factors involved in the digital transformation of organizations, for which it was necessary to review previous studies and build a model with its consequent validation of hypotheses. This research corresponds to the explanatory research level, with a non-experimental and cross-sectional design. The study was carried out in textile and clothing businesses in the city of Huancayo, which had been making their sales through the internet and had in turn incorporated digital technologies. The results made it possible to identify that factors such as talent and technology directly affect digital performance. While managers and culture indirectly influence digital performance (through other variables), reflecting their importance in the digital transformation process of organizations. Through this study, the key factors involved in the digital transformation process and the way they interact were identified, which represents valuable information to take into account when preparing the strategic plan for a successful digital migration of the organization.